2016
DOI: 10.2217/pme.15.57
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ Attitudes Toward Pharmacogenetic Testing Before and After Pharmacogenetic Education

Abstract: Aim:Our aim was to evaluate physicians' attitudes toward pharmacogenetic testing before and after pharmacogenetic education. Methods: In total, 12 physicians (∼40% response rate) completed a survey with eight questions on 10-point scales on their attitudes toward pharmacogenetic testing before and after a 1-h grand rounds presentation on pharmacogenetics. Differences in question scores overall, among training levels (resident/fellow/attending), and specific drugs (clopidogrel/simvastatin/warfarin) were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 31 publications
1
32
0
Order By: Relevance
“…Additionally, students enrolled in the pharmacy and medical schools at the University of Florida and University of Maryland received their personal pharmacogenetic genotype test results as part of their curriculum . TPP members continue to present at grand rounds, in‐services, and high‐profile domestic and international symposia, which have been shown to significantly improve attitudes toward pharmacogenetic testing and pharmacogenetic testing rates …”
Section: Resultsmentioning
confidence: 99%
“…Additionally, students enrolled in the pharmacy and medical schools at the University of Florida and University of Maryland received their personal pharmacogenetic genotype test results as part of their curriculum . TPP members continue to present at grand rounds, in‐services, and high‐profile domestic and international symposia, which have been shown to significantly improve attitudes toward pharmacogenetic testing and pharmacogenetic testing rates …”
Section: Resultsmentioning
confidence: 99%
“…Five of the 44 studies (11.4%) measured attitudes as a major outcome of the training programs. Four studies 12,25,27,52 reported positive attitudes toward genetics/ genomics in general; in the fifth study, 22 mental health providers exhibited mixed attitudes toward the use of genetic tests in clinical practice. For instance, in a basic genetics training program conducted in community health clinics, Kolb et al 12 found that, compared with the baseline and post-test data, 121 participating primary health-care providers reported a significantly positive change in attitude toward providing genetic services to their clients.…”
Section: Program Evaluationmentioning
confidence: 96%
“…Online modules and CDS tools often provide links to other educational resources (eg, PharmGKB, CPIC, and G2C2) . Various models, including ground rounds and web‐based continuing education modules, have shown positive outcomes related to pharmacogenomic education . However, inherent barriers such as provider time constraints and learner attitudes, together with financial and personnel resources, necessitate a multimodal approach to delivering education.…”
Section: Pharmacogenomics Educationmentioning
confidence: 99%